1985
DOI: 10.1093/nar/13.18.6663
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence and genome organization of carnation mottle virus RNA

Abstract: (1,2). This isometric virus infects a wide range of host plants and is one of the simplest of all eukaryotic infectious agents with regard to genome complexity. The smal 1 genome size renders CarMV highly accessible to molecular genetic analysis; thus, CarMV may serve as a useful model to understand RNA plant virus genome structure, function, and regulation.The structure and coding properties of CarMV RNA have been subjects of recent study. In addition to genome-length RNA, two major subgenomic species are pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
66
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(73 citation statements)
references
References 29 publications
(22 reference statements)
7
66
0
Order By: Relevance
“…There is another small ORF, encoding the p9 protein, which overlaps the p80RF and the start of the p38 ORF but is in the same reading frame as the replicase. In TCV, it has recently been shown that these proteins are involved in virus movement as previously suggested for TCV and CarMV (Guilley et al, 1985;Carrington et al, 1989;Hacker et al, 1992).…”
supporting
confidence: 52%
See 1 more Smart Citation
“…There is another small ORF, encoding the p9 protein, which overlaps the p80RF and the start of the p38 ORF but is in the same reading frame as the replicase. In TCV, it has recently been shown that these proteins are involved in virus movement as previously suggested for TCV and CarMV (Guilley et al, 1985;Carrington et al, 1989;Hacker et al, 1992).…”
supporting
confidence: 52%
“…The genomic sequence of CCFV-CL was translated and compared with those of TCV, carnation mottle (CarMV), and melon necrotic spot (MNSV) carmoviruses (Carrington et al, 1989;Guilley et al, 1985;Riviere & Rochon, 1990) using the Staden (1982), SEQ and GCG programs in a VAX 3100 computer.…”
mentioning
confidence: 99%
“…No obvious sequence similarities that might suggest the function of MNSV p7A were found in the databases searched. It has been suggested that CarMV p7 and TCV p8 may be involved in virus transport (Guilley et al, 1985;Carrington et al, 1989).…”
Section: Mnsv (40) a I H G S W T S A I S H D~s K I~vmentioning
confidence: 99%
“…Fig. 3 shows a comparison between the translation strategies of TNV-D, TNV-A (Meulewaeter et al, 1990), carnation mottle carmovirus (CarMV; Guilley et al, 1985) and cucumber necrosis tombusvirus (CNV; Rochon & Tremaine, 1989). In TNV-A, the p8 and p60RFs are in the same reading frame whereas in TNV-D, the p7a and p7b (shown as a stippled box) ORFs are out of frame but are shown together for comparative purposes and simplicity.…”
Section: Possible Translation Strategymentioning
confidence: 99%
“…The genomic organization of TNV-D as compared with that of CNV (Rochon & Tremaine, 1989), CarMV (Guilley et al, 1985) and TNV-A (Meulewaeter et al, 1990) is shown in Fig. 3.…”
Section: Comparison Of the Genomic Organization And Translation Stratmentioning
confidence: 99%